Any lessons for today? Exchange-rate stabilisation in Greece and South-East Europe between economic and political objectives and fiscal reality, 1841-1939 - Matthias Morys (European Historical Economics Society (EHES), 2015)
We add a historical and regional dimension to the debate on the Greek debt crisis. Analysing the 1841-1939 exchange-rate experience of Greece, Bulgaria, Romania and Serbia/Yugoslavia, we find surprising parallels to the present: repeated cycles of entry to and exit from gold, government debt build-up and default, and financial supervision by West European countries. Periods of stable exchange-rates were more short-lived than in any other part of Europe as a result of "fiscal dominance", i.e., a monetary policy subjugated to the treasury's needs. Granger causality tests show that patterns of fiscal dominance were only broken under financial supervision, when strict conditionality scaled back the influence of treasury; only then were central banks able to pursue a rule-bound monetary policy and, in turn, stabilize their exchange-rates. Fiscal institutions have remained weak in the case of Greece and are at the heart of the current crisis. A lesson for today might be that the EU-IMF programmes – with their focus on improving fiscal capacity and made effective by conditionality similar to the earlier South-East European experience – remain the best guarantor of continued Greek EMU membership. Understandable public resentment against "foreign intrusion" needs to be weighed against their potential to secure the long-term political and economic objective of exchange-rate stabilisation.
Keywords: N13; N14; N23; N24; E63; F34; 330; fiscal dominance; gold standard; financial supervision; South-East Europe